Preparation of self-solidifying polymeric depots from PLEC-PEG-PLEC triblock copolymers as an injectable drug delivery system - Wannarong Khamlao (2018)
Copolymers of (D,L-lactide-random-ε-caprolactone)-block-poy(ethylene glycol)-block-(D,L-lactide-random-ε-caprolactone) or PLEC were explored as materials for injectable drug delivery system. A series of six PLECs were successfully synthesized with varied D,L-lactide (LA) content (0, 10 and 20%) and molecular weight (20 and 50 kDa). All polymers were able to form depots with more than 90% encapsulation efficiency of trypan blue leading to the loading density as high as 27% w/w. The variation of trypan blue loading, LA content and molecular weight were found to have profound effects on trypan blue release profiles. Even though, GPC and SEM confirmed the higher degradation of PLEC chains, trypan blue release rate and burst release was greater as the content of hydrophilic moiety, i.e. LA, was decreased. This was primarily due to the smooth and dense surface and cross-section of PLEC depots. The results from this study suggest a possible application of these depots as injectable, self-solidifying drug delivery systems. © Springer Science+Business Media B.V. 2012.